Analysis of A below Knee Prosthetic Socket - K. Radi, Samira; F .Neama, Haider (Journal of Engineering and Sustainable Development, 2008)
This paper presents the analysis of a below-knee prosthetic socket for successful amputation, comfort, and stability. Seven different design models are created by changing the socket wall thickness, enlarging pressure relief areas of the socket, and changing the material.The model designs are implemented by the finite element program, ANSYS. Useful information on stresses and deflections are obtained and a final design of the socket is selected